A Point Prevalence Survey of Antibiotic Use in 18 Hospitals in Egypt - Maha Talaat; Tamer Saied; Amr Kandeel; Gehad A. Abo El-Ata; Amani El-Kholy; Soad Hafez; Ashraf Osman; Mohamed Abdel Razik; Ghada Ismail; Sherine El-Masry; Rami Galal; Mohamad Yehia; et al. (MDPI AG, 2014)
Inappropriate antibiotic use leads to increased risk of antibiotic resistance and other adverse outcomes. The objectives of the study were to determine the prevalence and characteristics of antibiotic use in Egyptian hospitals to identify opportunities for quality improvement. A point prevalence survey was conducted in 18 hospitals in March 2011. A total of 3408 patients were included and 59% received at least one antibiotic, with the most significant use among persons <12 years and intensive care unit patients (p < 0.05). Third generation cephalosporin were the most commonly prescribed antibiotics (28.7% of prescriptions). Reasons for antibiotic use included treatment of community-(27%) and healthcare-associated infections (11%) and surgical (39%) and medical (23%) prophylaxis. Among surgical prophylaxis recipients, only 28% of evaluable cases received the first dose within two hours before incision and only 25% of cases received surgical prophylaxis for <24 h. The prevalence of antibiotic use in Egyptian hospitals was high with obvious targets for antimicrobial stewardship activities including provision of antibiotic prescription guidelines and optimization of surgical and medical prophylaxis practices.